The Role of IPSAS Application in Meeting Voters Yearnings - Shakirat Adepeju Babatunde (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- How does the IPSAS application affect Accountability and government effectiveness in Nigeria? Motivation- Inadequate disclosure of public account information has made a mess of public resources management regarding accountability and government effectiveness, necessitating rational actions for minimising cover-up of unethical practices in government. This study employs Tawiah (2022); Schmidthuber et al. (2022) to tailor IPSAS and governance concepts. It creates unique constructs of voters' turnout rates to measure government effectiveness and buttress Accountability. Idea- This study examines governance status based on public support through the voters' election turnout. It anchors the research variables on the institutional and theoretical framework of IPSAS and public responses to government effectiveness Data- It analyses 1999 to 2020, a 22-year-time series data covering before and after the IPSAS application; obtained from the World Bank Development Indicators data bank and the National Assembly Federal Republic of Nigeria resources. Tools- It uses descriptive, ordinary least square regression, correlation statistical, and econometric analyses. Findings- During IPSAS application period, Accountability improves while government effectiveness declines. Whereas, during GAAP period, Government accountability progresses while Presidential and House of Representatives elections negatively influence the government's effectiveness. Hence, the Voters' turnout dwindled. Contributions- A unique methodology involving voters, political parties, officeholders, foreign direct investors and gross domestic products in studying government financial reporting standards. Combination of two regimes of GAAP and IPSAS to demonstrate deeper analyses of accounting standards and public performance evaluation. Evidences that the hidden economic problems associated with resource misallocation are aggravated during the IPSAS period.
Keywords: H11; H21; H83; 650; Accountability; Government Effectiveness; IPSAS application; Institutional framework; IPSAS; Voters' Turnout